You are on page 1of 13

General Relativity: Homework 3 Solutions

1. Carroll Problem 3.1


Verify these consequences of metric compatability (

= 0):

= 0

= 0
Solution:
To verify the rst claim, recall that g

is the inverse of g

so that we have:
g

= n
where n is the dimension of the manifold. Now take the covariant derivative of both sides, noting that the
covariant derivative of a constant is zero,

(g

) = 0
g

) + (

)g

= 0
g

) = 0
And therefore

= 0.
To verify the second claim note Carroll equations 2.69 and 2.70 which imply

= n!
where n is the dimension of the manifold we are working over, and we are assuming that the metric is
Lorentzian (this assumption is uneccessary, its just why the negative sign is there, all we really need is that
the right-hand side is a constant). Taking the covariant derivatives of both sides we obtain

) = 0
Since

is an honest to goodness tensor, we may relate it to

by factors of the g

. Specically we
have

= g

By inserting this expression into the covariant derivative, using the Leibniz rule, and the fact that

= 0,
we arrive at the expression

) =

) = 0
Replacing the dummy indices in the second expression we arrive at
2

= 0
Multiplying both sides by

implies

= 0.
1
2. Carroll Problem 3.5
Consider a 2-sphere with coordinates (, ) and metric
ds
2
= d
2
+ sin
2
d
2
(a) Show that lines of constant longitude ( = constant) are geodesics, and that the only line of constant
latitude ( = constant) that is a geodesic is the equator ( = /2).
(b) Take a vector with components V

= (1, 0) and parallel-transport it once around a circle of constant
latitude. What are the components of the resulting vector, as a function of ?
Solution:
(a) To verify a curve is a geodesic we need to write the geodesic equation for this metric. First we need
the connection coecients, to which we appeal to Carroll equation (3.154), although it is a worthwhile
exercise to derive these for yourself. The nonzero coecients are:

= sin cos

= cot
Now we may write out the geodesic equation(s):
d
2
x

d
2
+

dx

d
dx

d
= 0
which give us the two equations:
d
2

d
2
sin cos
_
d
d
_
2
= 0
d
2

d
2
+ 2 cot
d
d
d
d
= 0
In the case that is a constant the rst equation reads
d
2

d
2
= 0, while the second equation is trivial.
Thus the curve x

= (, ) is a geodesic.
If instead we assume is a constant we get:
sin cos
_
d
d
_
2
= 0
d
2

d
2
= 0
Since we cant set
d
d
= 0 (because then the curve would just be a point), if the rst equation is
to be satised we must have = /2 (note that = 0 is not a well-dened coordinate). Therefore
x

= (/2, ) is a geodesic, and in fact it is the only geodesic (up to reparameterization) where is
constant.
(b) In order to parallel transport a vector we must choose a path (with parameterization) to transport
along. Any parameterization will work, however it is best to keep it simple, so choose x

= (, ). Now
we must solve the parallel transport equation:
d
d
V

+

dx

d
V

= 0
Note that
dx

d
= (0, 1) so that we get the two equations:
dV

d
sin cos V

= 0 (1)
2
dV

d
+ cot V

= 0 (2)
To solve this system dierentiate (2) with respect to (keeping in mind that is a constant), solve for
dV

d
, plug it into (1) and do a little algebra to obtain:
d
2
V

d
2
+ cos
2
V

= 0
We can do the same procedure (dierentiating (1) and plugging into (2)) to obtain a dierential
equation for V

:
d
2
V

d
2
+ cos
2
V

= 0
These equations are just those for a simple harmonic oscillator (with frequency cos ), so the form of
the solutions are:
V

() = Acos(cos ) + B sin(cos )
V

() = C cos(cos ) + Dsin(cos )
Now apply the boundary condition V (0) = (1, 0) which gives us that A = 1 and C = 0. To pin down
the last two constants, appeal to one of the original equations, say (1):
dV

d
= sin cos V

cos (sin(cos ) + B cos(cos )) = sin cos (Dsin(cos ))
sin(cos ) + B cos(cos ) = sin Dsin(cos )
Comparing the coecients of sin(cos ) and cos(cos ) on both sides we see that we must have B = 0
and D =
1
sin
. Thus we have the solution to the parallel transport equation:
V

() =
_
cos(cos ),
sin(cos )
sin
_
Plugging in = 2 we see that after parallel transporting V

around a circle of constant latitude
the resulting vector is:
V

(2) =
_
cos(2 cos ),
sin(2 cos )
sin
_
As a check we can see that the vector is unchanged (i.e. V

(2) = (1, 0)) if we parallel transport
around the equator ( = /2), as expected.
3. Carroll Problem 3.6
A good approximation to the metric outside the surface of the Earth is provided by
ds
2
= (1 + 2)dt
2
+ (1 2)dr
2
+ r
2
(d
2
+ sin
2
d
2
)
where
=
GM
r
may be thought of as the familiar Newtonian gravitational potential. Here G is Newtons constant and M
is the mass of the Earth. For this problem may be assumed to be small.
(a) Imagine a clock on the surface of the Earth at a distance R
1
from the Earths center, and another clock
on a tall building at distance R
2
from the Earths center. Calculate the time elapsed on each clock as
a function of the coordinate time t. Which clock moves faster?
3
(b) Solve for a geodesic corresponding to a circular orbit around the equator of the Earth ( = /2). What
is d/dt?
(c) How much proper time elapses while a satellite at radius R
1
(skimming along the surface of the Earth,
neglecting air resistance) completes one orbit? You can work to rst order in if you like. Plug in
the actual numbers for the radius of the Earth and so on to get an answer in seconds. How does this
number compare to the proper time elapsed on the clock stationary on the surface?
Solution:
(a) For a clock on the surface of the Earth, the world-line (parameterized by t) is x

= (t, R
1
, , t), where
is the angular velocity of the Earth ( =
rad
12 hrs
). Now calculate the proper-time:
=
_
t
0
_
g

dx

dt
dx

dt
dt

=
_
t
0
_
(1 + 2) R
2
1
sin
2

2
dt

=
_
1
2GM
R
1
R
2
1
sin
2

2
t
Now lets reinstate the factors of c.
2GM
R1
has units of velocity squared, so we should divide that by c
2
.
The same goes for the second term under the square root. Also note that R
1
<< c, so we can drop
that term (we also have R
2
1

2
<<
2GM
R1
, which justies leaving in
2GM
R1
), leaving us with:
=
_
1
2GM
c
2
R
1
t
For the clock on a tall building we replace R
1
with R
2
and see that the proper-time is decreased. Note
that this eect is purely due to the dierence in gravitational potential (the eect due to time dilation
associated with the dierence in speeds is negligible).
(b) To nd a geodesic we must look at the geodesic equations. In fact, because we are looking for a specic
type of geodesics, namely one with constant radius, r and = /2 we do not need to look at all of the
equations. First look at the geodesic equation for x

= r which reads:
d
2
r
d
2
+
r

dx

d
dx

d
= 0
Keeping in mind that we are restricting ourselves to paths with constant r and constant , this expres-
sion simplies to

r
tt
_
dt
d
_
2
+
r

_
d
d
_
2
+ 2
r
t
d
d
dt
d
= 0
Now calculate just the necessary connection coecients

r
tt
=
1
2
g
r
(
t
g
t
+
t
g
t

g
tt
) =
1
2
g
rr

r
g
tt

r
tt
=
1
2
_
1
(1 2)
_

r
(1
2GM
r
) =
GM
r
2
(1 2)

=
1
2
g
r
(

) =
1
2
g
rr

r
g

=
1
2
_
1
(1 2)
_

r
(r
2
sin
2
) =
r sin
2

(1 2)

r
t
=
1
2
g
r
(

g
t
+
t
g

g
t
) = 0
4
Now the geodesic equation reads:
GM
r
2
(1 2)
_
dt
d
_
2

r sin
2

(1 2)
_
d
d
_
2
= 0

d
d
=
_
GM
r
3
dt
d
(3)
We still havent found the geodesic, to do so now consider the equation for x

= t:
d
2
t
d
2
+
t

dx

d
dx

d
= 0
Again, considering only paths such that r is constant and = /2 this simplies to:
d
2
t
d
2
+
t
tt
_
dt
d
_
2
+
t

_
d
d
_
2
+
t
t
dt
d
d
d
= 0
Now look at the equation for the necessary connection coecients

=
1
2
g
tt
(

g
t
+

g
t

t
g

)
and we can see that for , {t, } the connection coecients will all be zero. The geodesic equation
is now just
d
2
t
d
2
= 0
the simplest non-trivial solution to which is t = . Taking this as our parameterization, (3) then
implies:
d
dt
=
_
GM
r
3
Putting it all together, the (up to reparameterization) geodesic corresponding to a circular orbit (of
radius r) around the equator ( = /2) is:
x

(t) = (t, r, /2,


_
GM
r
3
t)
(c) For the satellite skimming the surface of the Earth (at = /2) we have that the elapsed proper-time
for a complete orbit is:
=

1
2GM
c
2
R
1

R
2
1

2
c
2
2

where =
_
GM
R
3
1
and we have included the term related to the motion of the satellite because it is on
the same order as the gravitational potential. Plugging in the expression for we have
= 2

1
2GM
c
2
R
1

R
2
1
c
2
GM
R
3
1
_
R
3
1
GM
= 2
_
R
3
1
GM

3R
2
1
c
2
= 2

(6.371 10
6
m)
3
(6.674 10
11
Nm
2
kg
2
)(5.972 10
24
kg)

3(6.371 10
6
m)
2
(2.998 10
8
m
s
)
2
= 5061s
Now to calculate the the elapsed proper-time for the clock stationary on the surface of the Earth,
borrow the result from part (a), setting = /2.
=
_
1
2GM
c
2
R
1
2

= 2
_
1
2GM
c
2
R
1
_
R
3
1
GM
= 2
_
R
3
1
GM

2R
2
1
c
2
5
= 2

(6.371 10
6
m)
3
(6.674 10
11
Nm
2
kg
2
)(5.972 10
24
kg)

2(6.371 10
6
m)
2
(2.998 10
8
m
s
)
2
= 5061s
For a clock stationary on the surface the elapsed proper-time (during the orbit of the satellite) is
exactly the same as that of the satellite! This is because both are the same distance from the center of
the Earth, and therefore they both have the same gravitational potential (and the eect due to time
dilation clearly has a negligible eect).
To fully convince ourselves that this eect is due purely to gravity, consider a stationary clock at the
top of Mount Everest ( 9000m high). Repeating the previous calculation we obtain = 5072s.
Gravity slows the passage of proper-time! A true means for slowing the eects of aging.
4. Carroll Problem 3.13
Find explicit expressions for a complete set of Killing vector elds for the following spaces:
(a) Minkowski space, with metric ds
2
= dt
2
+ dx
2
+ dy
2
+ dz
2
.
(b) A spacetime with coordinates (u, v, x, y) and metric
ds
2
= (dudv + dvdu) + a
2
(u)dx
2
+ b
2
(u)dy
2
where a and b are unspecied functions of u. This represents a gravitational wave spacetime. (Hints,
which you need not show: there are ve Killing vectors in all, and all of them have a vanishing u
component K
u
.)
Be careful, in all of these cases, about the distinction between upper and lower indices.
Solution:
All answers are vectors with upper indices.
(a) First note that all of the metric components are independent of t, x, y, z and therefore the four trans-
lations of those coordinates correspond to symmetries of the metric. These symmetries are generated
by the four Killing vectors:
T

= (1, 0, 0, 0)
X

= (0, 1, 0, 0)
Y

= (0, 0, 1, 0)
Z

= (0, 0, 0, 1)
To see that each of these satisfy
(
K
)
= 0 rst note that all of the connection coecients vanish for
the Minkowski metric, and therefore
(
K
)
=
(
K
)
. Since all of the components of these vectors are
constant, all of the partial derivatives will vanish as well and the Killing vector condition is satised.
Next consider the three generators of purely spatial rotations (see Carroll pages 138-9 for a more
detailed discussion of these). They are (with lowered indices):
Rx

= (0, 0, z, y)
Ry

= (0, z, 0, x)
Rz

= (0, y, x, 0)
Lets explicitly verify that Rx

satises the Killing vector condition. First check that

Rx

= 0, but
this is clear since the
th
component of Rx

is independent of the
th
coordinate (e.g. the y component
is independent of y). Next condsider terms where = , in fact the only non-trivial combination is:

y
Rx
z
+
z
Rx
y
=
y
(y) +
z
(z) = 1 + (1) = 0
6
Similar calculations show that all three of these vectors satisfy the Killing vector condition. All thats
left to do is raise their indices, but thats easy for this metric:
Rx

= (0, 0, z, y)
Ry

= (0, z, 0, x)
Rz

= (0, y, x, 0)
Finally, by looking at the calculations for the three rotation generators, lets guess that the three
vectors corresponding to
Bx

= (x, t, 0, 0)
By

= (y, 0, t, 0)
Bz

= (z, 0, 0, t)
are also Killing vectors (corresponding to boosts along each axis). Again, verify by following the same
argument as for the rotations. Lets check the non-trivial case for Bx

t
Bx
x
+
x
Bx
t
=
t
(t) +
x
(x) = 1 + (1) = 0
Now we need to again raise the indices, and in this case we need to be wary of the metric we are using:
Bx

= (x, t, 0, 0)
By

= (y, 0, t, 0)
Bz

= (z, 0, 0, t)
In all we have 10 Killing vectors, which is in agreement with the fact that the Poincare group (isometries
of the Minkowski metric) is 10 dimensional.
(b) In order to verify Killings equation we will need to calculate the connection coecients, a quick
observation and use of the hints will let us get away without calculating all of the coecients. Since,
as the hints indicate, the u-component of all of the Killing vectors is zero, by lowering the index,
K
u
g

= K
v
, we see that this implies K
v
= 0 for all Killing vectors. Therefore, by looking at the
covariant derivative of a 1-form

we conclude that we do not need to calculate


the
v

coecients (upper index equals v). We do however need to calculate the rest of them.
We will proceed with the variational technique, that is consider variations of the integral (Carroll eqn.
3.49)
I =
1
2
_
g

dx

d
dx

d
d =
1
2
_
(2
du
d
dv
d
+ a
2
(u)
_
dx
d
_
2
+ b
2
(u)
_
dy
d
_
2
)d
To get the coecients with upper index u, we will actually need to consider variations of v (this is due
to the cross terms in the metric). Under variations v v + v the only term in the integrand that
changes is
dv
d

dv
d
+
d(v)
d
and therefore the variation in I is
I =
1
2
_
2
du
d
d(v)
d
=
_
d
2
u
d
2
vd
where the second equality comes from integrating by parts. Requiring that the variation vanishes we
are left with
d
2
u
d
2
= 0
which implies that all coecients with upper index u vanish,
u

= 0.
Now we want the coecients with upper index x, for which we consider variations x x +x. Under
such variations the only change in the integrand is
_
dx
d
_
2

_
dx
d
+
d(x)
d
_
2
=
_
dx
d
_
2
+ 2
dx
d
d(x)
d
+ O(x
2
)
7
Therefore the variation of the integral (up to rst order in x) is
I =
_
a
2
(u)
dx
d
d(x)
d
d
Integrating by parts we obtain
I =
_
_
a
2
(u)
d
2
x
d
2
+ 2a(u)
da
du
du
d
dx
d
_
d
Setting the variation equal to zero leads to the equation
a
2
(u)
d
2
x
d
2
+ 2a(u)
da
du
du
d
dx
d
= 0

d
2
x
d
2
+
2
a(u)
da
du
du
d
dx
d
= 0
Now we may read o the connection coecients

x
ux
=
x
xu
=
1
a(u)
da
du
Similarly we obtain

y
uy
=
y
yu
=
1
b(u)
db
du
Now that we have all of the necessary connection coecients we can now go about nding/guessing the
Killing vectors. We readily obtain three of them by noting that the metric has no explicit dependence
on the coordinates v, x, y, which implies that it is invariant under translations of those coordinates and
therefore we have that the vectors (in (u, v, x, y) coordinates)
V

= (0, 1, 0, 0)
X

= (0, 0, 1, 0)
Y

= (0, 0, 0, 1)
are Killing vectors. Lets verify that all three of these vectors satisfy Killings equation. First lets
show it for V

. We need to be careful because lowering the index changes the components around,
specically V

= (1, 0, 0, 0). Now we have

= 0
u

(1) = 0
where weve used that all of the components of V

are constants, hence all of the partial derivatives


vanish, and that all
u

= 0.
Next we should verify that X

satises Killings equation (and by similar calculations, that Y

does
as well). This is a little trickier than in the previous case, because now lowering the index gives us
X

= (0, 0, a
2
(u), 0).

a
2
(u)
x

The most interesting cases we need to check are = u, = x and vice versa. In the former we get

u
X
x
=
u
a
2
(u) a
2
(u)
_
1
a(u)
da
du
_
= a(u)
da
du
Switching indices we have

x
X
u
=
x
(0) a
2
(u)
_
1
a(u)
da
du
_
= a(u)
da
du
8

u
X
x
+
x
X
u
= a(u)
da
du
a(u)
da
du
= 0
Unfortunately those are the only obvious symmetries of the metric, and as the hint suggests, we still
have two more Killing vectors to nd. To nd the last two vectors lets explore a bit with the covariant
derivative. Look at

u
K
u
=
u
K
u
+

uu
K

Since all of the relevant connection coecients with lower labels uu are zero, we see that in order
for K

to satisfy Killings equation we must have


u
K
u
= 0, that is, K
u
must be independent of u.
Following the same logic with
x
K
x
we see that K
x
must be independent of x. Now lets look at the
implications of the cross terms.

x
K
u
+
u
K
x
=
x
K
u

xu
K

+
u
K
x

ux
K

=
x
K
u
+
u
K
x

2
a(u)
da
du
K
x
In order for K

to satisfy Killings equation we must have

u
K
x

2
a(u)
da
du
K
x
=
x
K
u
Because K
u
is independent of u, and K
x
is independent of x, the right hand side must equal a constant
(i.e. K
u
= x for some constant , which we can set to -1 without loss of generality). Therefore we
have the linear rst-order dierential equation

u
K
x

2
a(u)
da
du
K
x
= 1
Following the procedure for solving such equations (i.e. looking it up in your favorite dierential
equations book) we solve for the integrating factor (u)
(u) = exp
__

2
a(u)
da
du
du
_
= exp{2 ln |a(u)| + C} = Da
2
(u)
for some constant D. Now that we have the integrating factor the solution is given by
K
x
= (u)
1
_
_
(u)du
_
=
1
D
a
2
(u)
_
Da
2
(u)du = a
2
(u)
_
1
a
2
(u)
du
Note that for a problem with boundary conditions there should be some constants hanging around
from the improper integrals, however since we do not have any such conditions we can just seek the
simplest such solution. Thus with lower indices our solution is
K

=
_
x, 0, a
2
(u)
_
du
a
2
(u)
, 0
_
You should check for yourself that this indeed solves the equation. Raising the indices we get the
Killing vector
K

=
_
0, x,
_
du
a
2
(u)
, 0
_
Following the same procedure we obtain the nal Killing vector

=
_
0, y, 0,
_
du
b
2
(u)
_
9
5.
In ve-dimensional spacetime, x
M
= (x

, y), the Randall-Sundrum metric is given by


ds
2
= g
MN
dx
M
dx
N
= e
2ky

dx

dx

+ dy
2
where k is a constant and

=diag(1, 1, 1, 1).
(a) Calculate the Christoel connection coecients. (Rather than direct calculation via Eq. (3.27), you
will probably nd it easier to use the variational technique!)
(b) Calculate the Riemann tensor, Ricci tensor, and Ricci Scalar.
(c) Is this a maximally symmetric space? Verify by using Eq. (3.191).
Solution:
(a) Using the variational technique, we look for stationary points in the integral
I =
1
2
_
g

dx

d
dx

d
d =
1
2
_ _
e
2ky
_

_
dx
0
d
_
2
+
_
dx
1
d
_
2
+
_
dx
2
d
_
2
+
_
dx
3
d
_
2
_
+
_
dy
d
_
2
_
d
First lets consider variations x
1
x
1
+ x
1
. Under such variations the only change in the integrand is
_
dx
1
d
_
2

_
dx
1
d
+
d(x
1
)
d
_
2
=
_
dx
1
d
_
2
+ 2
dx
1
d
d(x
1
)
d
+ O
_
(x
1
)
2
_
Therefore, up to rst-order in x
1
the variation of the integral is
I =
1
2
_
_
2e
2ky
dx
1
d
d(x
1
)
d

d
Integrate by parts with u = e
2ky dx
1
d
and dv =
d(x
1
)
d
giving us
I = e
2ky
dx
1
d
x
1
|
boundary

_ _
d
2
x
1
d
2
e
2ky
2ke
2ky
dx
1
d
dy
d
_
x
1
d
Demanding that the variation of x
1
vanish at the boundary, and setting the variation of the integral equal
to zero we get the following equation
d
2
x
1
d
2
2k
dx
1
d
dy
d
= 0
which implies the non-zero
1
ij
are

1
14
=
1
41
= k
where we use the convention that y = x
4
. Generalizing this calculation for other is we get

i
i4
=
i
4i
= k, i = 0, 1, 2, 3
Note that the minus sign in front of
_
dx
0
d
_
2
does not aect the result of the calculation because there are no
o-diagonal terms in the metric and we are setting the variation equal to zero.
Now consider variations y y +y. Every term in the integrand will change as a result of this variation.
One should look familiar by now
_
dy
d
_
2

_
dy
d
+
d(y)
d
_
2
=
_
dy
d
_
2
+ 2
dy
d
d(y)
d
+ O
_
(y)
2
_
The other terms involve the exponential factor, whose variation is
e
2ky
e
2k(y+y)
= e
2ky
(1 2k y + O(y
2
))
10
Therefore the variation of the integral is (dropping terms O(y
2
))
I =
1
2
_ _
2k e
2ky
y
_

_
dx
0
d
_
2
+
_
dx
1
d
_
2
+
_
dx
2
d
_
2
+
_
dx
3
d
_
2
_
+ 2
dy
d
d(y)
d
_
d
Integrating the last term by parts and dropping the boundary term we arrive at
I =
_ _
k e
2ky
_

_
dx
0
d
_
2
+
_
dx
1
d
_
2
+
_
dx
2
d
_
2
+
_
dx
3
d
_
2
_

d
2
y
d
2
_
y d
I = 0 k e
2ky
_

_
dx
0
d
_
2
+
_
dx
1
d
_
2
+
_
dx
2
d
_
2
+
_
dx
3
d
_
2
_
+
d
2
y
d
2
= 0
Now we read o the following connection coecients

4
00
= ke
2ky

4
ii
= ke
2ky
, i = 1, 2, 3
All other connection coecients equal 0.
(b) Since the Riemann tensor has so many terms, even if you include symmetries, it is often helpful to
turn this calculation into a matrix calculation (matrices are the natural way of manipulating several equa-
tions at once). For this particular metric it isnt actually all that dicult to just do this term by term, since
there are only so many non-zero connection coecients, however for more complicated metrics this technique
comes in quite handy.
The denition of the Riemann tensor is:
R

Dene the matrices


(

(R

= R

where is the row index and is the column index. R

should not be confused with the Ricci tensor R

.
What we have dened is merely a matrix that is useful for doing computations. With these denitions the
denition of the Riemann tensor can be recast as the matrix equation
R

The components of the matrices can be written as


(
0
)

= k
0

4
ke
2ky

0
(
i
)

= k
i

4
+ ke
2ky

i
; i = 1, 2, 3
(
4
)

= k
3

i=0

i
Also note that because of the antisymmetry of the Riemann tensor in the last two indices, it suces to
consider just the case where < .
Lets do some example calculations:
R
01
=
0

1

1

0
+
0

1

1

0
Because none of the connection coecients depend on x
0
or x
1
the derivative terms drop out and we have
R
01
=
_
_
_
_
_
_
0 0 0 0 k
0 0 0 0 0
0 0 0 0 0
0 0 0 0 0
ke
2ky
0 0 0 0
_
_
_
_
_
_
_
_
_
_
_
_
0 0 0 0 0
0 0 0 0 k
0 0 0 0 0
0 0 0 0 0
0 ke
2ky
0 0 0
_
_
_
_
_
_

_
_
_
_
_
_
0 0 0 0 0
0 0 0 0 k
0 0 0 0 0
0 0 0 0 0
0 ke
2ky
0 0 0
_
_
_
_
_
_
_
_
_
_
_
_
0 0 0 0 k
0 0 0 0 0
0 0 0 0 0
0 0 0 0 0
ke
2ky
0 0 0 0
_
_
_
_
_
_
11
=
_
_
_
_
_
_
0 k
2
e
2ky
0 0 0
k
2
e
2ky
0 0 0 0
0 0 0 0 0
0 0 0 0 0
0 0 0 0 0
_
_
_
_
_
_
Doing the same calculation for R
02
and R
03
we nd the following non-zero components to the Riemann
tensor
R
0
i0i
= R
i
00i
= k
2
e
2ky
; i = 1, 2, 3
The calculation is also very similar (only diering by a minus sign) for R
ij
; i < j = 1, 2, 3 resulting in the
components
R
i
jij
= k
2
e
2ky
; R
j
iij
= k
2
e
2ky
; i < j = 1, 2, 3
Now lets try the calculation for R
14
R
14
=
1

4

4

1
+
1

4

4

1
=
y
_
_
_
_
_
_
0 0 0 0 0
0 0 0 0 k
0 0 0 0 0
0 0 0 0 0
0 ke
2ky
0 0 0
_
_
_
_
_
_
+
_
_
_
_
_
_
0 0 0 0 0
0 0 0 0 k
0 0 0 0 0
0 0 0 0 0
0 ke
2ky
0 0 0
_
_
_
_
_
_
_
_
_
_
_
_
k 0 0 0 0
0 k 0 0 0
0 0 k 0 0
0 0 0 k 0
0 0 0 0 0
_
_
_
_
_
_

_
_
_
_
_
_
k 0 0 0 0
0 k 0 0 0
0 0 k 0 0
0 0 0 k 0
0 0 0 0 0
_
_
_
_
_
_
_
_
_
_
_
_
0 0 0 0 0
0 0 0 0 k
0 0 0 0 0
0 0 0 0 0
0 ke
2ky
0 0 0
_
_
_
_
_
_
=
_
_
_
_
_
_
0 0 0 0 0
0 0 0 0 k
2
0 0 0 0 0
0 0 0 0 0
0 k
2
e
2ky
0 0 0
_
_
_
_
_
_
Repeating the previous calculation for the other components we nd
R
0
404
= k
2
; R
4
004
= k
2
e
2ky
R
i
4i4
= k
2
; R
4
ii4
= k
2
e
2ky
; i = 1, 2, 3
All other terms not related to one of these by a symmetry vanish.
Now we calculate the Ricci tensor by the denition, but this is aided by the observation that R

is
equal to zero unless = . Therefore all of the o-diagonal terms are zero and our work is almost done.
R
00
= R

00
= R
1
010
+ R
2
020
+ R
3
030
+ R
4
040
Rewrite this in terms of the components that we have calculated:
R
00
= R
1
001
R
2
002
R
3
003
R
4
004
= k
2
e
2ky
+ k
2
e
2ky
+ k
2
e
2ky
+ k
2
e
2ky
= 4k
2
e
2ky
Proceeding in a similar manner we nd
R
ii
= R

ii
= 4k
2
e
2ky
; i = 1, 2, 3
R
44
= R

44
= 4k
2
Finally calculate the Ricci scalar
R = R

= g

12
where
g

=
_
_
_
_
_
_
e
2ky
0 0 0 0
0 e
2ky
0 0 0
0 0 e
2ky
0 0
0 0 0 e
2ky
0
0 0 0 0 1
_
_
_
_
_
_
So we get for the Ricci scalar
R = e
2ky
(4k
2
e
2ky
) + e
2ky
(4k
2
e
2ky
4k
2
e
2ky
4k
2
e
2ky
) + 1(4k
2
) = 20k
2
(c) A metric denes a maximally symmetric space if it satises Carroll eq. 3.191, which for a ve-dimensional
manifold reads:
R

=
R
20
(g

)
Luckily the metric is diagonal and so we only need to worry about the terms R

and the symmetry of


both expressions in the second pair of indices will take care of the rest. For i, j = 1, 2, 3; i = j we have
R
ijij
= g
ik
R
k
jij
= e
2ky
(k
2
e
2ky
) = k
2
e
4ky
Compare this with
R
20
(g
ii
g
jj
g
ij
g
ji
) =
20k
2
20
e
2ky
e
2ky
= k
2
e
4ky
Now consider i = 1, 2, 3
R
0i0i
= g
0k
R
k
i0i
= g
00
R
0
i0i
= e
2ky
(k
2
e
2ky
) = k
2
e
4ky
Compare with
R
20
(g
ii
g
00
g
i0
g
0i
) =
20k
2
20
e
2ky
(e
2ky
) = k
2
e
4ky
Now we just take care of the terms involving 4s, rst considering i = 1, 2, 3
R
i4i4
= g
ik
R
k
4i4
= g
ii
R
i
4i4
= (e
2ky
)(k
2
) = k
2
e
2ky
Compare with
R
20
(g
ii
g
44
g
i4
g
4i
) =
20k
2
20
e
2ky
(1) = k
2
e
2ky
...Just one last case to check
R
0404
= g
0k
R
k
404
= g
00
R
0
404
= e
2ky
(k
2
) = k
2
e
2ky
Compare with
R
20
(g
00
g
44
g
04
g
40
) =
20k
2
20
(e
2ky
)(1) = k
2
e
2ky
All cases check out, so this metric does indeed dene a maximally symmetric space.
13